Effect of Symmetry Error and Error Coupling Compensation on Meshing Characteristic of Herringbone Gear - Weiguo Li; Guangbin Yu; Hancheng Mao; Lin Fu (Jixie chuandong)
In order to study the effect of the symmetry error generated by processing on the herringbone character gear meshing transmission， improve the stability of the transmission， according to the structural characteristics of herringbone gear and gear geometry contact model， consider the tooth surface gap， force equilibrium conditions and axial displacement， the herringbone gear bearing contact analysis model of symmetry error is established. The influence of different symmetry error on the gear contact and axial vibration of a pair of herringbone gear is analyzed， and then a compensation method that uses coupling effect of axial assembling error and symmetry error is put forward. The research result shows that symmetry error seriously reduces the stability and reliability of herringbone gear transmission. The error coupling compensation can lower partial loaded and axial vibration caused by symmetry error which provides new methods for the optimization of transmission process and is of greatly significant to improve the dynamic characteristics of herringbone gear system.